PENGEMBANGAN DAN VALIDASI METODE KROMATOGRAFI CAIR KINERJA TINGGI UNTUK PENETAPAN KADAR CIPROFLOXACIN DALAM SPIKED PLASMA MANUSIA DAN APLIKASINYA UNTUK UJI BIOEKIVALENSI - , Anggun Aji Mukti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ciprofloxacin is a fluoroquinolone type antibiotic agent that is being widely used for the treatment of several bacterial infections. It exhibits broad spectrum antimicrobial activity against Gram negative and Gram positive bacteria. This study aims to develop and validate an HPLC method couple with a UV detection for determination of ciprofloxacin in spiked human plasma and its application for bioequivalence study. HPLC method using an RP-C18 column (Lachrom Hitachi, 250 x 4,6 mm., 5Î¼m), mobile phase of phosphate buffer (pH 3 Â± 0,1 ) : acetonitrile (87 : 13) , a flow rate of 1,5 mL / min with ultraviolet detection at 276,6 nm. The limid of detection is 0,07 Î¼g/mL. The regression equation are linear (r > 0,999) This method was successfully applied to bioequivalence study of two product of 500 mg ciprofloxacin. For bioequivalence study was obtained (90% CI) ratio of Cmax = 74,08-124,60%, (90% CI) AUCt(0-12) ratio = 83,53-122,14 % and (90% CI) ratio AUCt(0- ) = 86,07- 120,92%.